(untitled) (GYMNASIUM, 2017)
Our study deals with 3D kinematic analysis of human gait which is based on case study of women walking. The purpose of this research was using 3D kinematic analysis and obtaining very precise kinematic characteristics in chosen key phases of human gait. Specially we were interested in center of gravity movement. Adult healthy woman in age of 45 years was videotaped by 2 synchronised high speed cameras and analysed by biomechanists. Tested person has mostly sedentary style of life but she likes cycling and swimming activities. Step frequency was set by pace maker (frequency 90 steps/min), walking in amount of four steps was realised in laboratory conditions, on wooden ground and using sport shoes.